Microbial endolithic biofilms: A means of surviving the harsh conditions of the Antarctic - Ríos, Asunción de los; Wierzchos, Jacek; Sancho, Leopoldo G.; Grube, M.; Ascaso, Carmen (European Space Agency, 2002)
4 páginas y 7 figuras Much of the Antarctic continent's microbiota is restricted to endolithic microecosystems which harbour distinct microbial communities as biofilms. The lithic substrate and the microrganisms comprising these films are intimately linked, giving rise to complex mineral-microbe interactions. The Antarctic biofilms analysed in this study were characterised by the presence of extracellular polymer substances. Cyanobacteria appeared as key components of these biofilms in zones where there were no nearby lichen thalli. Financial support was provided by DGICYT projects ANT99-0680 and BOSS2000-1121 and "Acciones integradas" Spain-Austria funds (MCyT/ÖAD) Peer reviewed